Pengaruh Sistem Pendaftaran Online Via Mobile JKN Terhadap Kepuasan Pasien Rawat Jalan di Rumah Sakit X Kota Bandung - Farras Najla Wiloka; Ade Irma Suryani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Online registration system allows patients to register quickly and easily without having to queue and come to the hospital. It is recently known that users of online registration system are lower compared to manual registration system. This research intend to determine the effect of online registration system via Mobile JKN on outpatients’ satisfaction in Hospital X Bandung City. This research method is quantitative method. The population of this research were users of online registration system via Mobile JKN in March and April 2024 in total of 201 patients. The sample size used was calculated using the Slovin formula on 36 respondents which was determined using simple random sampling technique. The results of simple linear regression test obtained values 0,000 < 0,05 so it can be concluded that the variable of the online registration system via Mobile JKN has a significant effect on the outpatients’ satisfaction variable. It is recommended to do enhancement of quality and development for online registration system via Mobile JKN in purpose to make online registration to be more effective and efficient.